Targeting Receptor Tyrosine Kinases and Their Downstream Signaling with Cell‐Penetrating Peptides in Human Pulmonary Artery Smooth Muscle and Endothelial Cells. (5th November 2014) - Yu, Jun; Rupasinghe, Chamila; Wilson, Jamie L.; Taylor, Linda; Rahimi, Nader; Mierke, Dale; Polgar, Peter
<x xml:space="preserve">Abstract</x> Cell‐penetrating peptide (CPP) intracellular delivery of receptor signaling motifs provides an opportunity to regulate specific receptor tyrosine kinase signal transductions. We targeted tyrosine residues Y740 and Y751 of the PDGF receptor β (PDGFRβ) and Y1175 of the VEGF receptor 2 (VEGFR2). The Y740 and Y751 motifs activated ERK and Akt, while the Y1175 motif activated ERK. Targeting either Y740 or Y751 of the PDGFRβ in human pulmonary artery smooth muscle cells (HPASMC) effectively inhibited PDGF activation of ERK or Akt. Interfering with the Y751 region of the PDGFRβ proved more effective than targeting the Y740 region. The phosphorylation of Y751 of the CPP and the length and exact sequence of the mimicking peptide proved crucial. On the other hand, in human pulmonary artery endothelial cell phosphorylation of the VEGFR2 Y1175 CPP was not a determinant in blockage of ERK activation. Likewise, the length of the peptide mimic was not crucial with a very small sequence containing the Y1175 remaining effective. Physiologic proof of concept for the effectiveness of the CPP was confirmed by blockage of HPASMC migration in response to PDGF following culture injury. Thus targeted blockage of tyrosine kinase receptor signaling can be very effective.